What is the state of knowledge on preterm birth? - N. Dropińska; K. Chmaj-Wierzchowska; M. Wojciechowska; M. Wilczak (IMR Press, 2020)
Objective: Preterm delivery (PTD) is the leading cause of neonatal mortality and the most common reason for antenatal hospitalization. This study aimed at the assessment of the state of knowledge of women of childbearing age regarding PTD, including its risk factors and symptoms, as well as the procedure performed, and the factors influencing the level of knowledge of women about PTD. Materials and Methods: The study was carried out in the period between July 5-15, 2017 and a group of 93 women of childbearing age residing within the Wielkopolska area, attending obstetric and gynecological clinics. The survey questionnaire was constructed for the purpose of the study and contained questions on the issues related to PTD, including the risk factors and symptoms of PTD, a procedure performed for PTD, and complications faced by the neonate. Results: The sources of knowledge most frequently indicated by the surveyed women were family/friends (26.9%), magazines (28%), and physician (22.5%), while midwives (14%) and birthing school (8.6%) were indicated least frequently. A higher level of knowledge was found among the women who obtained information on PTD from a midwife, physician, and family/friends (χ2 = 22.618; p = 0.004). Conclusions: A higher level of knowledge on PTD was exhibited by women who obtained information on this issue from a midwife, physician, or family/friends. Therefore, there is a need to educate pregnant woman regarding the risk factors of PTD.